Congenital Megaoesophagus in a Pup- A case report - Abboori Sangeetha; Satish Kumar K (Indian Journal of Veterinary Medicine, 2024)
A 3 month old GSD pup was presented to VCC, CVSc, Rajendranagar, with history of vomiting for a couple of weeks. Deworming and vaccination was regular. Physical examination revealed emaciation and poor body score. Plain X Ray did not reveal any abnormality except ventral deviation of thoracic trachea. Barium contrast radiography revealed dilation of the oesophagus and the pup was diagnosed with congenital megaesophagus. Subsequently, the pup was managed with elevated feeding and dietary changes, which showed a marked improvement.